(3GdHOjYs - (3GSGeI Hf efbP , GSGeI Hf eQTO Hf Ydj Hf ebdO Hf fUQ Hf efbP GdcfGfj GdcdHj, CHh GdeXaQ,J (B584 (3g` s
(3ChdgG (B:s
(3gPG cJGH LeYJ ajg eG JaQb ai cJH GdYdeGA s
(3BNQgG (B:s
(3CPcGQ ddSeGM ef Cgd s
(3eUhQ Yf fSNI HGdGScfOQjIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B282s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1401s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs